Rumen fistulation in sheep and goats - Mohd Jelan, Zainal Aznam; Alimon, Abdul Razak; Osman, A. (Persatuan Doktor Veterinar Malaysia, 1986)
The rumen of three adult local sheep and six local goats werefistulated onthe. left paralumbar fossa by two different techniques. In the first technique on three goats, a circular area of skin and underlying tissues were removed to expose the rumen wall Simple interrupted sutures were placed around the periphery of the incised tissues together with the wall of rumen resulting in adhesion of these tissues after 10 days. A rubber fistula was inserted after removing the necrosed rumen wall. In the second . technique on three sheep and three goats, a pair of stainlesssteel bars were used to clamp the exteriorized portion of the rumen that was brought out through an incision. The exteriorized part necrosed and sloughed after eight days leaving an opening into the rumen through which a rubber cannula was permanently inserted. Both techniques resulted in well formed fistula with, except in one, no post-operative complication. The second technique was quicker and relatively simpler to perform.